(untitled) (Experimental biology, 2022)
Brown or leaf rust is one of the devastating wheat diseases, caused by the fungus Puccinia triticina, which can lead to crop losses and also to deterioration of grain quality. The brown rust resistance of soft and durum wheat is a prerequisite for consistently high yields. Eleven samples (of local and Russian selection) were used as a research material. In order to study wheat resistance to leaf rust, seven genes were selected – Lr9, Lr10, Lr14, Lr22a, Lr28, Lr34, and Lr67. Based on the results of the molecular screening, it was found that both soft and durum wheat varieties have Lr10, Lr22a, Lr34 and Lr67 genes in their genomes and are carriers of both effective and ineffective resistance genes. The marker linked to the Lr9 gene was identified only in the control sample Novosibirskaya 29, which indicates the absence of this gene in durum wheat materials. Even so durum wheat samples are protected by genes Lr10, Lr14 and highly efficient gene Lr28. Wheat varieties in which resistance genes have been amplified can be pyramidized with other resistance genes and successfully used in appropriate breeding programs.